Case Report: Successful treatment of advanced hepatocarcinoma with the PD-1 inhibitor Camrelizumab - Ye, Wenling; Cai, Lihong; Zhang, Minjie; Wu, Yali; Sun, Huina; Wang, Yan-Dong; Xia, Yubing (Frontiers in Immunology, 2023)
Primary liver cancer is characterized by closely related with chronic liver inflammation, thereby reversing hypoxic immunosuppressive microenvironment of tumor cell growth by immunotherapy drug is a potentially effective strategy. Camrelizumab is an anti-PD-1 antibody being developed by Jiangsu Hengrui Pharmaceuticals Co., Ltd. We reported a case of an adult critical Chinese patient with primary hepatocellular carcinoma and lung metastasis completely responding to Camrelizumab, most of the lesions were stable and no new lesions occurred after 1-year treatment, which provides us to reconsider the therapeutic effect of Camrelizumab on such patients. Camrelizumab had a safety profile for the patient in our case report, except for the occurrence of RCCEP. This case provides the evidence of the effective antitumor activity and manageable toxicities of Camrelizumab for patients with advanced hepatocellular carcinoma, which was the first application as far as we know.